An intelligent selection method based on game theory in heterogeneous wireless networks - Salih, Y.K.; See, O.H.; Ibrahim, R.W. (Wiley, 2016)
In next-generation networks, users can optimize the choice with seamless transfer of different access technologies to maximize cost saving and improve quality of service. In such heterogeneous wireless environments, users equipped with multimode wireless devices that can access rich media services via one or more access networks. These networks may differ in terms of monetary cost, coverage range, technology, available bandwidth, energy usage and so on. The new challenge faced by network operators is to ensure users always connect to the best available network, whenever they want and wherever they are or another word to stay Always-Best-Connected. Therefore, a new intelligent method is proposed here to optimize vertical handover in selection processes to ensure Always-Best-Connected in heterogeneous wireless networks. The proposed solution identifies a new game network selection model for choosing the best connections from different candidate wireless networks. The selected network should satisfy the typical user demands. The proposed selection model is implemented by using the non-cooperative game model. The proposed solution is evaluated through in-depth analysis and simulation-based testing. Results clearly prove that the proposed solution exhibits the highest performance compared with other solutions.